2020
DOI: 10.7554/elife.52985
|View full text |Cite
|
Sign up to set email alerts
|

Aire-dependent genes undergo Clp1-mediated 3’UTR shortening associated with higher transcript stability in the thymus

Abstract: The ability of the immune system to avoid autoimmune disease relies on tolerization of thymocytes to self-antigens whose expression and presentation by thymic medullary epithelial cells (mTECs) is controlled predominantly by Aire at the transcriptional level and possibly regulated at other unrecognized levels. Aire-sensitive gene expression is influenced by several molecular factors, some of which belong to the 3’end processing complex, suggesting they might impact transcript stability and levels through an ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…This observation, along with the apparently incomplete representation of peripheral structures and absence of excessive numbers of novel splice isoforms in mTEC, suggests that TEC undertake a selective program of alternative splicing to ensure the accurate representation of a subset of the peripheral splice isoform repertoire. We hence conclude that transcript structures in mTEC are primarily shaped by a small number of splicing and mRNA processing factors (Guyon et al 2020) and that mTEC do not rely on "promiscuous" mechanisms to promote and increase splice isoform diversity, as previously suggested (Keane et al 2015). Rather (and assuming that our observations hold in humans), a limited thymic representation of peripheral splice isoforms is consistent with the concept that tissue-specific isoforms are relevant sources of autoantigens in immune-mediated diseases (Evsyukova et al 2010;Juan-Mateu et al 2016;Newman et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…This observation, along with the apparently incomplete representation of peripheral structures and absence of excessive numbers of novel splice isoforms in mTEC, suggests that TEC undertake a selective program of alternative splicing to ensure the accurate representation of a subset of the peripheral splice isoform repertoire. We hence conclude that transcript structures in mTEC are primarily shaped by a small number of splicing and mRNA processing factors (Guyon et al 2020) and that mTEC do not rely on "promiscuous" mechanisms to promote and increase splice isoform diversity, as previously suggested (Keane et al 2015). Rather (and assuming that our observations hold in humans), a limited thymic representation of peripheral splice isoforms is consistent with the concept that tissue-specific isoforms are relevant sources of autoantigens in immune-mediated diseases (Evsyukova et al 2010;Juan-Mateu et al 2016;Newman et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, knockdown of PCF11 in human and mouse cells also caused down-regulation of both closely spaced and short genes, suggesting that such genes might be especially dependent upon PCF11 for proper 3′ end maturation ( 18 , 19 ). In conjunction with studies showing that CLP1 and PCF11 levels vary between tissues ( 17 , 18 ), these findings suggest that CFII may not be universally required for pre-mRNA cleavage, but rather contribute to cleavage in a transcript- and/or cell-type specific manner. Whether the Clp1 R140H mutation influences mRNA 3′ processing and gene expression is unknown.…”
supporting
confidence: 57%
“…Whether CFII is universally required for pre-mRNA cleavage cannot be readily ascertained because both its constituent proteins are absolutely required for cell survival; however, many studies have demonstrated that CFII influences where cleavage occurs. Knockdown of CLP1 in human cell lines and mouse thymic cells increased the relative use of distal PASs, while in contrast, Clp1 knockdown in mouse myoblast cells caused a slight bias toward use of proximal PASs ( 14 17 ). Knockdown of PCF11 in human and mouse cells and knockout in zebrafish also influenced PAS selection, with a shift toward use of distal sites ( 14 16 , 18 , 19 ).…”
mentioning
confidence: 94%
“…It also induces topoisomerase II-dependent double-strand breaks, the editing and splicing of RNA [ 26 , 33 , 34 ]; promotes the release of stalled RNA polymerase-II [ 35 ] and enhances the binding of super-enhancers to ‘orderly relaxed’ chromatin [ 36 , 37 ]. Furthermore, AIRE-dependent RNAs are preferentially stabilised through the 3′ end processing complex that generates short 3′ UTRs and protects against miRNA-mediated degradation [ 38 ]. In the mouse, the spectrum of AIRE-driven TRAs is further broadened by cooperation of AIRE with the transcription factor, Fezf2, and the chromatin modulator, Chd4 [ 39 ].…”
Section: The Thymic Medulla and Autoimmunitymentioning
confidence: 99%